2009
DOI: 10.1029/2008wr006959
|View full text |Cite
|
Sign up to set email alerts
|

A method for estimating surface transient storage parameters for streams with concurrent hyporheic storage

Abstract: [1] Application of transient storage models has become popular for characterizing hydrologic and biogeochemical processes in streams. The typical transient storage model represents exchange between the main channel and a single storage zone, essentially lumping together different exchange processes. Here we present a method to inform a transient storage model that accounts for two storage zones (2-SZ) to discriminate between surface transient storage (STS) exchange and exchange with hyporheic transient storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
148
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(151 citation statements)
references
References 60 publications
(103 reference statements)
3
148
0
Order By: Relevance
“…Application of a multi-zone transient storage model (e.g. Choi et al (2000), Marion et al (2008) and Briggs et al (2009)), would allow for solute retention in the surface zone to be separated from solute retention in the hyporheic zone and potentially also the parafluvial zone, particularly if pore water samples were collected from the hyporheic zone during the experiment. Previous studies have reported that residence times within the hyporheic zone do not have an exponential distribution (an assumption which underlies the OTIS model) (Cardenas, 2008;Cardenas et al, 2004;Haggerty et al, 2002;Sawyer and Cardenas, 2009).…”
mentioning
confidence: 99%
“…Application of a multi-zone transient storage model (e.g. Choi et al (2000), Marion et al (2008) and Briggs et al (2009)), would allow for solute retention in the surface zone to be separated from solute retention in the hyporheic zone and potentially also the parafluvial zone, particularly if pore water samples were collected from the hyporheic zone during the experiment. Previous studies have reported that residence times within the hyporheic zone do not have an exponential distribution (an assumption which underlies the OTIS model) (Cardenas, 2008;Cardenas et al, 2004;Haggerty et al, 2002;Sawyer and Cardenas, 2009).…”
mentioning
confidence: 99%
“…Since data collection methods to support parameter estimation in two zone transient storage modeling are evolving (e.g., Briggs et al 2009;Neilson et al, 2010a,b), the need for flexibility when incorporating dynamic external information is underscored in model calibration particularly when dealing with both local and global scales. This type of flexibility is not available when optimization algorithms rely solely on the options encoded to solve the problem, which is the case for most single objective algorithms (e.g., nonlinear gradient-based search algorithms such as the Levenberg-Marquardt algorithm (Marquardt, 1963, used by Hil, 1998Doherty, 2005;Poeter et al, 2005), evolutionary algorithms (Duan et al, 1992;Deb, 2001) or Bayesian approaches (Metropolis et al, 1953;Hastings, 1970;Doherty, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Second, transient storage models assume that any mass entering a storage zone will return to the main channel at the location of entrainment, thereby neglecting mass transfer through relatively long hyporheic flow paths . Third, reach-averaging a stream's total transient storage parameters couples the effects of STS and HTS, and does not provide information on the relative influence of surface and hyporheic exchange on solute entrainment and retention (Choi et al, 2000;Briggs et al, 2009). Lastly, precise relationships between transient storage, solute exchange, and stream hydromorphic parameters have not been identified as different studies produce contrasting results.…”
Section: T R Jackson Et Al: a Fluid-mechanics Based Classificationmentioning
confidence: 99%
“…Transient storage is the short-term storage of fluid due to the exchange of solutes and suspended particulates in the main flow with (1) recirculating in-stream flow structures, referred to as surface transient storage (STS); and/or (2) the hyporheic zone, referred to as hyporheic transient storage (HTS) (Bencala and Walters, 1983;Boulton et al, 1998;Briggs et al, 2009). By definition, the total transient storage in a stream is the sum of STS and HTS.…”
Section: Introductionmentioning
confidence: 99%